1995
DOI: 10.1248/bpb.18.1526
|View full text |Cite
|
Sign up to set email alerts
|

Selective Induction of Cell Death in Cancer Cells by Gallic Acid.

Abstract: Gallic acid (3,4,5-trihydroxybenzoic acid) is a naturally occurring plant phenol obtained by the hydrolysis of tannins and is know to show some pharmacological activities. In screening anti-cancer agents in traditional Chinese medicines, gallic acid was found to show cytotoxicity against all cancer cells that we examined in this study (IC50s: 4.8-13.2 micrograms/ml). Gallic acid was found to show cytotoxicity against primary cultured rat hepatocytes and macrophages, and lesser cytotoxicity against fibroblasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
148
1
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(160 citation statements)
references
References 1 publication
4
148
1
4
Order By: Relevance
“…A similar result has already been reported against rat hepatoma (dRLh-84) cells by Inoue et al 12) We have also observed the phenomenon that the antiproliferative activity of caffeic acid is lowered by esterification. 1) In spite of structural differences, 5 and 3 showed similar activity.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…A similar result has already been reported against rat hepatoma (dRLh-84) cells by Inoue et al 12) We have also observed the phenomenon that the antiproliferative activity of caffeic acid is lowered by esterification. 1) In spite of structural differences, 5 and 3 showed similar activity.…”
supporting
confidence: 91%
“…And a carboxyl group is likely to be necessary in order for gallic acid to show selectivity to cancer cells, since pyrogallol killed not only dRLh-84 cells, but also primary cultured rat hepatocytes. 12) Furthermore, they also disclosed that the cell death induced by gallic acid was accompanied by internucleosomal DNA fragmentation characteristic of apoptosis. 13) In order to clarify in more detail the structure-antiproliferative activity relationship of gallic acid derivatives, we tested for the antiproliferative activity of ellagic acid and three related phenol carboxylic acids (Fig.…”
mentioning
confidence: 99%
“…5) In addition, the study of the signaling pathway indicated that intracellular Ca 2Ï© may play an important role in GD-1 and GD-3-induced apoptosis as well as GA-induced apoptosis, but ROS was involved only in GA-induced apoptosis. 5) To clarify the mechanism by which GDs induce apoptosis and the difference in the signaling pathway elicited by GDs or GA, we asked in the present study whether GDs activate caspase-3, a downstream caspase in the signaling pathway leading to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Gallic acid is cytotoxic to cancer cells and has anti-inflammatory and antimutagenic properties (2,3). Gallic acid has been described as an excellent free radical scavenger and as an inducer of differentiation and programmed cell death in a number of tumor cell lines (4,5). Recently, it was revealed that gallic acid from rose flowers exhibits antioxidative effects even in senescence-accelerated mice and can restore the activities of catalase and gluthatione peroxidase (6).…”
Section: Introductionmentioning
confidence: 99%